ICTs for conservation agriculture: influence of actor positioning in knowledge networks in Laikipia and Machakos counties, Kenya - Achora, Janet C.; Sseguya, H.; Kyazze, Florence Birungi; Mkomwa, S.; Okello, D. (2018)
Knowledge networks play a significant role in the transfer of innovations such as conservation agriculture. In this paper, we examine the position of actors in the network and socio-economic factors influencing use of ICTs. ICTs potentially enable information to reach large numbers of farmers. We collected data through 298 household surveys, 29 key informant interviews and five focus group discussions. We used social network analysis for centrality measures. To statistically test the relationship between socio-economic factors and use of ICTs, we used multinomial logistic regression analysis. Results suggest that gender and land under conservation agriculture (p=<0.05) significantly influence use of radio, TV and mobile phones. Education (p=.024) was more likely to influence use of print media. Age (p > 0.05) was not a statistically significant factor. Positions of influence were occupied by extension officers (20%) and farmers (41%). The study recommends the use of ICTs with conventional approaches in CA knowledge networks.